Exploring harm in psychotherapy: Perspectives of clinicians working with children and young people. Issue 4 (26th September 2020) - Castro Batic, Barbara; Hayes, Dan
Abstract: Aims: The potential for harm to occur from talking therapies has been acknowledged in academic literature. However, there is a paucity of research when it comes to exploring this phenomenon when working with young patients. This study explores clinicians' perspectives on harm from talking therapies when working with children and young people. Method: Eleven clinicians were interviewed on the types of harm that could occur from talking therapies, as well as the potential mechanisms. Data were analysed inductively using thematic analysis. Results: Two themes were identified around types of harm: 'clinical deterioration' and 'retraumatisation'. Additionally, four groups of mechanisms were identified: 'Administrative factors', 'Relationship factors', 'Therapist factors' and 'Contextual factors'. Discussion: Clinicians are able to identify some specific types of harm when working with children and young people and understand how these could occur. The clinical implications of these findings are explored, along with limitations and directions for future research.